Involvement of old crustal materials during formation of the Sakhalin Island (Russian Far East) and its paleogeographic implication: Constraints from detrital zircon ages of modern river sand and Miocene sandstone. (15th September 2017) - Zhao, Pan; Li, Jia-jin; Alexandrov, Igor; Ivin, Vitaly; Jahn, Bor-ming
Graphical abstract: Highlights: Detrital zircon ages of Cenozoic sediments in the Sakhalin Island are firstly reported. Old crustal materials have been involved in the crust of the Sakhalin Island. Crustal nature of the Sakhalin Island may be related to the South China Craton. Abstract: In order to decipher crustal nature of the Sakhalin Island in Russian Far East, we carried out detrital zircon U-Pb age analyses on Miocene sandstone and river sand from the longest river (Poronay River) of the Sakhalin Island. The detrital zircon data from two river sand samples display similar age distribution patterns with a dominant Mesozoic age group, subordinate age peaks at 1.8 Ga and 2.5 Ga, and a few Paleozoic and Neoproterozoic grains. The Miocene sandstone shows age peaks at 22, 84, 260 and 497 Ma, respectively, and a few Paleo-proterozoic grains. These age groups indicate that abundant old crustal materials have been involved in the crustal formation of the Sakhalin Island. Detrital zircon result reveals two episodes of post-accretion magmatism from the Sakhalin Island in ages of 37 Ma and 22–21 Ma. They can be correlated with coeval post-accretion magmatic events in the Hokkaido Island, supporting the geological correlation between the Sakhalin Island and the Hokkaido Island. Comparison of detrital zircon dating result from the Sakhalin Island with those from surrounding blocks and cratons in eastern Asia allows us to propose two possible sources in eastern Asia: the Bureya-Jiamusi-Khanka block with the Sikhote-Alin orogenic belt to its west and the South China Craton. The detrital zircon result indicates that the formation of the Sakhalin Island should be close to the East Asia continent, rather than as an independent intro-oceanic island arc within the Pacific Ocean. Similar to formation of the Japanese islands, the South China Craton may have played an important role during formation of the Sakhalin Island.